Pengembangan Bahan Ajar Mata Kuliah Maos Naskah Jawi Carik - Ekowati, Venny Indria; Mulyani, Hesti; Nurhidayati, Nurhidayati (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2021)
This research is a continuation of the first-year research resulting from an analysis of the needs, design, and develop teaching materials in the form of draft modules. The research then continued with the second-year research aimed at (1) describing the quality of teaching materials for maos (reading) the script of Jawi carik sekar in accordance to the expert judgment, (2) describing the test results of teaching materials for maos (reading) lectures of the script of Jawi carik sekar, (3) describing the final product of teaching materials for maos the script of Jawi carik sekar. It is the implementation of the ADDIE model for research and development (Dick & Carry). The media development procedures in the first year include analysis, design, and development with the initial product in the form of draft modules. The media development procedures in the second year include implementation and evaluation. The validation of modules was conducted by experts in teaching materials and media. The average rating from materials experts was 88.8% and from the media experts was 95.2%. The assessment by both experts falls within the criteria of praiseworthy. Modules are tested in a small class of 15 students of semester 4 during Maos (reading) lectures of the script of Jawi Carik Sekar. The average score of students’ opinion on the developed module was 80.1% with the criteria of very respectable.